2013
DOI: 10.3390/ma6031072
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Mechanical Behavior of Textile Heating Fabric Based on Silver Coated Polymeric Yarn

Abstract: This paper presents a study conducted on the thermo-mechanical properties of knitted structures, the methods of manufacture, effect of contact pressure at the structural binding points, on the degree of heating. The test results also present the level of heating produced as a function of the separation between the supply terminals. The study further investigates the rate of heating and cooling of the knitted structures. The work also presents the decay of heating properties of the yarn due to overheating. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…In another study, it was reported that the fabrics knitted with silver yarn along with elastomeric yarn could generate sufficient heat to warm-up the body. Those fabrics could be used to manufacture personal heating garments that can generate heat in relation to applied voltage (Hamdani, Potluri, & Fernando, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was reported that the fabrics knitted with silver yarn along with elastomeric yarn could generate sufficient heat to warm-up the body. Those fabrics could be used to manufacture personal heating garments that can generate heat in relation to applied voltage (Hamdani, Potluri, & Fernando, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the three-dimensional structure of the carrier surface (cotton woven fabric), constituting a sort of ''scaffolding,'' the deposited CNT network also acquires a 3D character. These ''smart fabrics'' are very interesting in terms of their utilization as lightweight, wearable, flexible conducting materials for a wide range of energy and environmental device applications, including electromagnetic shielding (AlShabib et al 2012), antennas (Hertleer et al 2009;Kennedy et al 2009;Lee et al 2011;Yang et al 2007), microwave absorbers (Park et al 2006), resistive heating elements (Fischer et al 2011;Hamdani et al 2013;Yang et al 2010), ultracapacitors (Jost et al 2011), batteries , water filtration (Schoen et al 2010), microbial fuel cells (Xie et al 2011) and printed electronics (Andersson et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For a knitted structure that is locked in the wale direction and the course direction, the electrical current is through the feet of the stitches in the sinker loop; obviously, contact resistance between stitch and stitch is positive correlative with the sinker loop length. Hamdani et al 15 gave some equations for calculating the sinker loop length for PSF, RSF, and ILK. The sinker loop length per stitch of PSF is equal to one quarter of the stitch length, RSF is a double-layer structure having two planes of stitches, and ILK can be assumed to have two sinker loop paths; hence, the sinker loop length of RSF and ILK is more length than that of PSF, considering the thickness of KHF, RSF, and ILK is more thick than PSF as shown in Table 1.…”
Section: Measurement Of Power Consumption Of Khfmentioning
confidence: 99%
“…Liu Hao et al 14 fabricated a flexible and waterproof heating membrane by pouring modified nano-SiC/thermoplastic polyurethane solution into a mold with 0.05 mm diameter silver filaments and investigated the performances of the heating membranes by analyzing parameters such as Fourier transform infrared spectra, infrared temperature images, and thermal conductivity, etc. Hamdani et al 15 conducted on a study of the thermo-mechanical properties of knitted structures, the methods of manufacture, the effect of contact pressure at the structural binding points, on the degree of heating, and utilized infrared images to study the heat distribution over the surface of the knitted fabric. Wang et al 16,17 investigated the heating efficiency of an electrically heated vest (EHV), and acquired the correlation between power and environment temperature to provide the consumer a thermal comfort condition.…”
mentioning
confidence: 99%